There is no bank lending channel! - Luka Bajec; Johann Graf Lambsdorff (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2006)
The bank lending channel (BLC) has found entrance into standard economic textbooks. But the approach, as presented by Bernanke and Blinder [1988] operates with lopsided loan demand, money demand and money supply functions. This invalidates the idea that potential changes in the supply of loans may impact on aggregate demand for goods and services. Above, a reduction of loans may restrict an individual investors, but the macroeconomic logic of the IS curve suggests that such a constraint is not binding.
Keywords: 330